System językowy w umyśle a ekspresja mowy – zastosowanie ruchomego alfabetu w terapii - Sedivy-Mączka, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*66.02px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.964643);" role="presentation">Case studies of children with autism indicate <span dir="ltr" style="left: calc(var(--scale-factor)*240.87px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.969306);" role="presentation">that there are still many patterns in therapy<span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.983901);" role="presentation"> and that assessing the abilities of non-speaking children is a <span dir="ltr" style="left: calc(var(--scale-factor)*303.71px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991036);" role="presentation">huge problem. The search <span dir="ltr" style="left: calc(var(--scale-factor)*66.33px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0381);" role="presentation">for individually-adapted communication <span dir="ltr" style="left: calc(var(--scale-factor)*237.21px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03466);" role="presentation">strategies should be emphasised. Writing <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00818);" role="presentation">offers great opportunities for communication, however, it is often not offered to <span dir="ltr" style="left: calc(var(--scale-factor)*389.93px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05237);" role="presentation">non<span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*174.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998718);" role="presentation">speaking children, especially those with profound perceptual disorders.